Sensory Characteristics, Nutrient Content, and Microbial Load of Rice Eel (Monepterus albus) Tocino, Flavored With Fruit Extracts - Ladipe, Halem Karenez Y.; Angeles Jr., Isagani P.; Pataueg, Arjay B.; Ame, Evelyn C.; Ballad, Emma L.; Castro, Marites R.; Asprec, Mary Joy L. (Department of Food Science and Biotechnology, Faculty of Agriculture Technology, Universitas Brawijaya, 2025)
This study aimed to evaluate the sensory characteristics, nutrient content, and microbial load levels of Rice eel tocino flavored with different fruit extracts. Four experimental fish tocino were formulated to contain O. niloticus + 0%fruit extract (C0), M. albus + 2.26% Philippine lime (T1), M. albus + 2.26% Lemon (T2), and M. albus + 2.26% Orange (T3). Sensory evaluation and descriptive analysis were used for sensory characteristics. FDA standards and aerobic plate count were used for nutrient content and microbial analysis. All treatments were done in triplicate and were subjected to ANOVA with a post hoc test. Results show that sensory attributes in all treatments were perceived as “liked very much”. Nutrient analysis in all formulated treatments has shown an acceptable protein content of 26%-30%. Total fat ranged from 0%-3%, while total carbohydrates ranged from 2%-4.7%. All treatment groups showed acceptable limits of microbial levels (<106 cfu/g) until 32 days of storage.